2015
DOI: 10.1007/s12663-015-0812-3
|View full text |Cite
|
Sign up to set email alerts
|

Quest for an Ideal Route of Intubation for Oral and Maxillofacial Surgical Manoeuvres

Abstract: This present study concluded that the surgical access and visibility was immensely improved by following the anaesthetic and surgeon factors in conjunction with algorithms described for uneventful oral and maxillofacial surgical procedures. Further, this has also substantially minimized the influence of the 'route of intubation' on 'surgical technique' and vice versa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…One report of 634 elective maxillofacial surgeries found that 579 patients were intubated nasally. 17 Given that many authors advocate for fiberoptic nasal intubation over conventional nasotracheal intubation, 18 there appears to be ample need for FOI in oral and maxillofacial surgery. Although our hood is especially beneficial for awake FOI because of expected coughing and aerosol generation, this protocol is equally effective for both awake and sleep patients by either oral or nasal route of FOI.…”
Section: Discussionmentioning
confidence: 99%
“…One report of 634 elective maxillofacial surgeries found that 579 patients were intubated nasally. 17 Given that many authors advocate for fiberoptic nasal intubation over conventional nasotracheal intubation, 18 there appears to be ample need for FOI in oral and maxillofacial surgery. Although our hood is especially beneficial for awake FOI because of expected coughing and aerosol generation, this protocol is equally effective for both awake and sleep patients by either oral or nasal route of FOI.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were operated under general anesthesia with fiberoptic nasotracheal intubation. 8 Initially fibrous bands were incised deep to connective tissue extending posteriorly from the pterygomandibular raphe and/or anterior faucial pillars including buccinator muscle to as far as corner of the mouth anteriorly depending on the extent of palpable fibrous bands. The fibrous bands were disentangled with finger dissection and manipulation until no restriction was felt.…”
Section: Methodsmentioning
confidence: 99%
“…[ 1 ] In the repair of cleft lip and palate, nasotracheal intubation would hinder with closure of muscle and mucosa. [ 2 ] Hence, oral intubation becomes more favorable in such clinical situations. In complex craniomaxillofacial trauma, the airway is secured through a tracheostomy.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5 6 7 ] Previous studies have undertaken endeavors to gather, examine, and denote a wide variety of aspects, to evaluate the optimal route of intubation that may be planned for different oral and maxillofacial surgical maneuvers. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%